Răspuns :
radicalul și puterea a doua se elimina
[tex] \sqrt{(2 - \sqrt{5}) {}^{2} } + \sqrt{(3 - \sqrt{5} ) {}^{2} } = \\ = |2 - \sqrt{5} | + |3 - \sqrt{5} | [/tex]
_________________________
[tex] \huge |2 - \sqrt{5} | [/tex]
[tex]2 = \sqrt{ {2}^{2} } = \sqrt{4} \\ \sqrt{4} < \sqrt{5} \\ 2 < \sqrt{5} [/tex]
Modulul va fi
[tex] \huge| \sqrt{5 } - 2 | [/tex]
_________________________
[tex] \huge |3 - \sqrt{5} | \\ 3 = \sqrt{ {3}^{2} }= \sqrt{9} \\ \sqrt{9} > \sqrt{5} \\ 3 > \sqrt{5} [/tex]
Modulul va fi
[tex] \huge \: |3 - \sqrt{5} | [/tex]
_____________________
Revenim la exercițiu
[tex] = \sqrt{5} - 2 + 3 - \sqrt{5} = \\ = - 2 + 3 = \\ \huge = 1[/tex]